PERAN GURU SEBAGAI EVALUATOR : STUDI PADA PEMBELAJARAN PPKN DI MA HIDAYATUS SHIBYAN PARIT NAâ€™IM - Amir, Muhammad Farizal; Utomo, Bambang Budi; Atmaja, Tomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is "The Role of Teachers As Evaluators (Study of PPKn in MA Hidayatus Shibyan P Na'im) 2017/2018 Academic Year. The purpose of the teacher's role as an evaluator was the role of the teacher as an evaluator in the learning process and learning outcomes in the PPKn learning at MA Hidayatus Shibyan P Na'im. Descriptive qualitative approach, Descriptive nature refered to (1) Collected data in the form of words or images and contains quotations from the data as an illustration to provide support for what is presented. Methods of collecting data or research instruments using observation, interviews and documentation. Analysis of the data used was data reduction, data presentation, and conclusion. In testing the validity of using the data credibility test, After conducting the process of collecting, processing, and analyzing the data, we found some results of the study that the role of the teacher as an evaluator was very large in improving student learning outcomes. This was due to the maximum efforts made by the teacher in carrying out evaluations, starting from careful planning towards evaluation, implementation and utilization of evaluation resultsÂ Keywords: Teacher's Role as Evaluator, Study on PPKn LearningÂ